2019
DOI: 10.3389/fpubh.2019.00297
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Cross-Cultural Similarities and Differences in Social Discounting for Gains and Losses

Abstract: Social discounting is when resource allocation decreases as social distance increases. Studies fitting different quantitative models to social discounting data have shown that a q-exponential function based on Tsallis' statistics best fits loss data, whereas a hyperbolic power function best fits gain data. However, a social discounting sign effect, where losses are discounted less than equivalent gains, has not been consistently found. This study fit four different quantitative social discounting models to gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Social distance is how close we psychologically feel to another individual. Social discounting researchers have consistently shown that sharing money decreases hyperbolically as a function of increasing social distance for individuals from many different cultures (Stegall et al, 2019). That is, we share a lot with the people we are closest to, but much less as social distance increases.…”
Section: Introductionmentioning
confidence: 99%
“…Social distance is how close we psychologically feel to another individual. Social discounting researchers have consistently shown that sharing money decreases hyperbolically as a function of increasing social distance for individuals from many different cultures (Stegall et al, 2019). That is, we share a lot with the people we are closest to, but much less as social distance increases.…”
Section: Introductionmentioning
confidence: 99%
“…The uniqueness, or lack thereof, should be studied in future research. Regardless of whether each type of personal information is unique, future studies should test whether other viable functions, such as hyperboloid (Rachlin, 2006) and q ‐exponential (Stegall et al, 2019) functions, to determine which function best fits the obtained data. Better data fits can lead to more accurate modelling and predictions about how much personal information an individual is willing to share, potentially in risky online situations.…”
Section: Discussionmentioning
confidence: 99%
“…Collectivism or social interdependence is thought to be stronger in Asian than in western societies (Leung and Iwawaki, 1988;Hui et al, 1991;Oyserman et al, 2002). Previous cross cultural studies have compared social discounting in Japanese and German students (Ishii and Eisen, 2018), Chinese and German students (Strombach et al, 2014) and Japanese and American students (Ito et al, 2011;Romanowich and Igaki, 2017;Stegall et al, 2019). Two studies found that western participants were more generous at close social distances but discounted more rapidly as social distance increased, and this was taken as evidence that the greater social cohesiveness of Asian societies was reflected by lower levels of social discounting (Strombach et al, 2014;Ishii and Eisen, 2018).…”
Section: Introductionmentioning
confidence: 99%